Recent Progress in Synthesis and Application of Biomass‐Based Hybrid Electrodes for Rechargeable Batteries. (17th November 2022) - Baskar, Arun V.; Singh, Gurwinder; Ruban, Ajanya M.; Davidraj, Jefrin M.; Bahadur, Rohan; Sooriyakumar, Prasanthi; Kumar, Prashant; Karakoti, Ajay; Yi, Jiabao; Vinu, Ajayan
Abstract: The rapid growth in electronic and portable devices demands safe, durable, light weight, low cost, high energy, and power density electrode materials for rechargeable batteries. In this context, biomass‐based materials and their hybrids are extensively used for energy generation research, which is primarily due to their properties such as large specific surface area, fast ion/electron kinetics, restricted volume expansion, and restrained shuttle effect. In this review, the key advancements in the preparation of biomass derived porous carbons using different synthesis strategies and their modifications with species such as heteroatoms, metal oxides, metal sulfides, silicon, and other carbon forms are discussed. The electrochemical performances of these materials and the ion storage mechanisms in different batteries including lithium‐ion, lithium–sulfur, sodium‐ion, and potassium‐ion batteries are discussed. Special attention will be paid to the challenges in using porous biomass‐derived carbons and the current strategies employed for maximizing the specific capacity and lifetime for battery applications. Finally, the drawbacks in current technology and endeavors for the future research and development in the field to catapult the performances of the biomass derived materials in order to equip them to meet the demands of commercialization are highlighted. Abstract : This review covers discussions on the development of porous carbon‐based hybrid materials from biomass for utilization in various types of rechargeable batteries. In terms of hybridization, various strategies such as heteroatom doping, metal/s, and metal oxide/s and hydroxides, metal sulfides, doping, Si/SiO2 modification are discussed with emphasis on their application in Li‐ion, Li–S, Li–metal, Li–Se, Na, and K batteries.